TRUMP VS JOKOWI: EXPLORING THE LEXICOGRAMMATICAL VARIATION OF HEAD OF STATES’ TWITTER COMMUNICATION - Putu Nur Ayomi (LITERA, 2021)
TRUMP VS JOKOWI: EXPLORING THE LEXICOGRAMMATICAL VARIATION OF HEAD OF STATES’ TWITTER COMMUNICATION Putu Nur AyomiUniversitas Mahasaraswati Denpasaremail: putu.nur.a@unmas.ac.id Abstract Unlike other social media such as Facebook or Instagram, which is usually used to connect people and maintain relationships, Twitter focuses on information sharing. This makes Twitter an ideal platform to discuss ideas and generate conversations around particular issues. This article explores and compares the lexicogrammatical choices made by President Donald Trump and Joko Widodo in a selection of their tweets. Guided by Systemic Functional Linguistics (SFL), this article explains the stylistic differences and their implications in the three metafunctions: ideational, interpersonal, and textual, including the language used for evaluation drawn from the Appraisal system network. The study reveals that Trump’s language is more spoken-like than that of Jokowi’s. Trump also employs various appraisal strategies to negatively evaluate his opponents and counter various adverse accusations addressed to him. Jokowi, on the other hand, uses more abstract written-like language and use more positive appraisal strategies mainly addressed to his government programs and plans amid the Covid-19 pandemic. The result of the study reveals that different individual lexicogrammatical choices can generate diverse representations and images.Keywords: lexicogrammar, metafunction, grammatical metaphor, appraisalTRUMP VS JOKOWI: MENDEDAH VARIASI LEKSIKOGRAMATIKAL KOMUNIKASI KEPALA NEGARA DI TWITTERAbstrak Berbeda dengan media sosial lain seperti Facebook atau Instagram yang biasanya digunakan untuk menghubungkan orang dan menjaga hubungan, Twitter berfokus pada berbagi informasi. Ini menjadikan Twitter platform yang ideal untuk mendiskusikan ide dan menghasilkan percakapan seputar masalah tertentu. Artikel ini membahas dan membandingkan pilihan leksikogramatikal dari Presiden Donald Trump dan Joko Widodo dalam kumpulan tweet mereka. Dengan panduan teori Linguistik Fungsional Sistemik, artikel ini menjelaskan perbedaan gaya bahasa kedua presiden dan implikasinya dalam ketiga metafungsi: Ideasional, Interpersonal, dan Tekstual, termasuk penggunaan bahasa sebagai sarana evaluasi yang diambil dari sistem Appraisal. Kajian ini mengungkapkan bahwa bahasa Trump lebih bercirikan bahasa lisan dibandingkan bahasa Jokowi. Trump juga menggunakan berbagai strategi Appraisal untuk mengevaluasi lawan politiknya secara negatif dan untuk melawan berbagai tuduhan negatif yang ditujukan kepadanya. Di sisi lain, Jokowi menggunakan bahasa yang lebih abstrak dan bercirikan bahasa tertulis serta menggunakan strategi Appraisal positif terutama yang ditujukan pada program dan rencana kerja pemerintahannya di tengah pandemi Covid-19. Hasil penelitian menunjukkan bahwa pilihan leksikogramatikal individual yang berbeda dapat menghasilkan representasi dan citra yang beragam.Kata kunci: leksikogramatika, metafungsi, metafora gramatikal, appraisal